عناصر اللياقة البدنية وعلاقتها بمستوى التحصيل الدراسي لدى تلاميذ التعليم الثانوي (15-18سنة): دراسة ميدانية بثانوية صلاح الدين الأيوبي باتنة - فرطاس، يوسف; يحياوى، السعيد Yahiawi, Alsaid (جامعة باتنة, 2015)
تهدف الدراسة إلى الكشف عن العلاقة بين عناصر اللياقة البدنية ومستوى التحصيل الدراسي لدى تلاميذ التعليم الثانوي وذلك لتوجيه برامج التربية البدنية والرياضية للاهتمام بعناصر اللياقة البدنية الأساسية التي ستكون لها علاقة قوية بمستوى التحصيل الدراسي الجيد. حيث استخدم الباحث المنهج الوصفي الارتباطي لملائمته وطبيعة الدراسة، فيما تكونت عينة الدراسة من 200 تلميذ اختيرت بطريقة عشوائية بسيطة من تلاميذ السنوات الثلاثة. استخدم الباحث مقياس عناصر اللياقة البدنية مصمم من طرف الدكتور محمد حسن علاوي، وبالنسبة للتحصيل تم جمع معدلات نهاية السنة الدراسية لأفراد العينة. وتمت معالجة البيانات إحصائيا باستخدام برنامج SPSS 20.
The purpose of this study was to examine the relationship between elements of physical fitness and the level of academic achievement, to pupils in secondary school (15-18 age), in order to guide the programs of physical education and sports to interest much to one of the elements of physical fitness that will have a strong relationship to the level of academic achievement. Where the researcher uses the descriptive approach by one of its forms which is the correlation. The sample of the study consisted of 200 pupils selected by random way from pupils in three years in secondary school. Two hundred 200 pupils completed the description physical fitness questionnaire, and Average end-of-the-year academic marks served as measurement of academic achievement. The data processing using a statistical program SPSS20. And we have reached to the following conclusions: 1. There is a positive relationship with significance between elements of physical fitness (muscular strength, endurance, flexibility, elegance) and the level of academic achievement to pupils in secondary school (15-18 age). 2. There is not a relationship with significance between speed and the level of academic achievement to pupils in secondary school (15-18 age).
Keywords: اللياقة البدنية -- التحصيل الدراسي -- طلاب المدارس الثانوية -- الجزائر، باتنة -- مدرسة صلاح الدين الأيوبي الثانوية